2021
DOI: 10.3390/microorganisms9071451
|View full text |Cite
|
Sign up to set email alerts
|

A Microencapsulated Mixture of Eugenol and Garlic Tincture Supplementation Mitigates the Effect of Necrotic Enteritis on Intestinal Integrity and Increases Goblet Cells in Broilers

Abstract: This study was conducted to examine the effects of a plant extract mixture, a microencapsulated product composed of eugenol and garlic tincture (PE), on intestinal health in broilers under necrotic enteritis (NE) challenge. A total of 960 d-old mixed-sex Cobb 500 chicks were randomly distributed to 48-floor pens housing 20 birds per pen. Six treatments were applied: UC, unchallenged control; CC, challenged control; PE, challenged group plus PE; AM, challenged group plus antimicrobial (AM); FAP, challenged grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…The microbiota results both in ileal and caecal contents have been reported in a previous paper( Kumar et al, 2021 ). The effects of NE challenge and PE on C. perfringens loads in ileal and caecal contents of broilers on d d16 are shown in Table 4 .…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The microbiota results both in ileal and caecal contents have been reported in a previous paper( Kumar et al, 2021 ). The effects of NE challenge and PE on C. perfringens loads in ileal and caecal contents of broilers on d d16 are shown in Table 4 .…”
Section: Resultssupporting
confidence: 75%
“…Moreover, birds fed PE had similar intestinal lesions and oocysts counts compared to the AM group further confirmed the beneficial effects of PE supplementation in diets on intestinal health. In addition, it has been shown that birds fed PE had improved intestinal integrity and increased mucin-secreting goblet cells ( Kumar et al, 2021 ) which can further confirm the protective effects of PE supplementation to the birds against NE. Cumulatively, these findings demonstrated the beneficial effects of PE to reduce the severity of clinical NE challenge on performance and intestinal health as evidenced by improved feed efficiency, livability and uniformity reduced ileal lesions, oocyst counts, and increased skin yellowness.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, Enterobacteriaceae counts followed the same decreasing trend following eugenol nanoemulsion dietary inclusion indicating its valuable effects against pathogenic bacterial species. Similarly reduced loads of Bacteroides species were observed in birds fed a microencapsulated product comprised of garlic and eugenol tincture (40). Moreover, feeding chickens on a product of plant EOs containing active components, such as eugenol decreased the abundance of cecal Enterobacteriaceae (104).…”
Section: Discussionmentioning
confidence: 94%
“…In another recent study, it was also noted that birds fed eugenol and garlic had reduced CLDN5 expression in male birds, and Bacteroides spp. in female birds, than in the control group [216], suggesting that eugenol and garlic supplementation mitigates the effect of necrotic enteritis by improving the intestinal health of birds.…”
Section: Eugenolmentioning
confidence: 79%